2015
DOI: 10.20396/san.v13i1.1841
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and functional foods. Current situation and prospect for developing countries

Abstract: This review updates and attempts to present the complex panorama of bioactive phytochemicals and functional foods. For such purpose and given the breadth of the field, it was necessary to survey a large volume of scientific literature. The different types of studies used to provide evidence for efficacy are described. The different groups of health-promoting substances (carotenoids, phenolic compounds, phytosterols and phytostanols, tocotrienols, organosulfur compounds, nondigestible carbohydrates) are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 156 publications
(155 reference statements)
0
31
0
2
Order By: Relevance
“…This colouration is related to the presence of carotenoids, which are the pigments responsible for most of the yellow and orange colours present in many fruits. High values for carotenoids are desirable because these compounds have antioxidant properties and are known to reduce the risk of development of degenerative diseases, such as cancer, cardiovascular disease, cataracts and macular degeneration (RODRIGUEZ et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This colouration is related to the presence of carotenoids, which are the pigments responsible for most of the yellow and orange colours present in many fruits. High values for carotenoids are desirable because these compounds have antioxidant properties and are known to reduce the risk of development of degenerative diseases, such as cancer, cardiovascular disease, cataracts and macular degeneration (RODRIGUEZ et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals which appear to have health promoting potential are tetraterpenoid pigments carotenoids, phenolic compounds (flavonoids, phytoestrogens and phenolic acids), phytosterols, phytostanols, tocotrienols, organosulfur compounds, and non-digestible dietary fiber. [12] Several investigators have reported antioxidant activities of many different green leafy vegetables and these activities are attributed to their polyphenolic compounds [8], [9], [11]. The observation of positive correlation of ntioxidant activity and polyphenol content in methanol extracts may be expected because of the enhanced extraction of compounds in the methanol.…”
Section: Resultsmentioning
confidence: 99%
“…A high intake of food rich in natural antioxidants has been shown to increase the antioxidant capacity of plasma and reduce the risk of development many chronic and degenerative diseases. [11], [12] Recent research also has shown that through complimentary action and effects of a complex mixture of phytochemical compounds in fruits and vegetables provide a protective effect on health than a single isolated phytochemical, meaning that a whole fruit or vegetable is better than a product made from them. The protective effect is attributed to many components including vitamin C, E, carotenoid pigments, phenolic compounds and other phytochemicals present in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that they are involved in mechanisms of action related to the carcinogenic metabolism, regulation of cell growth, inhibition of cell proliferation, among others (Rodriguez et al, 2006).…”
Section: Definition Classification and Importance Of Carotenoids In mentioning
confidence: 99%